Lantang Pangngan at Mate Malolle’ Funeral Ritual in Toraja : An Ethnography Study - Elim Trika Sudarsi; Nilma Taula’bi’; Yakub Tangdibiri’; Markus Deli Girik Allo (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This study aims to determine how the values of the Toraja philosophy are implemented in the lantang pangngan ritual and how the stages of the lantang pangngan ritual represent the identity of the Toraja traditional community. The researcher applied a qualitative method through an ethnographic design in this study. In choosing the research subjects, researchers applied purposive sampling techniques; the subjects were Toraja cultural experts. Data are collected and analyzed in observations and interviews. The data analysis technique in this study is a cyclical pattern. The results showed that the values of the Toraja philosophy that were implemented in the lantang pangngan ritual were to masayang: Tang dimaseanpa penawa and Kinallo: vehicles to puya. Then, the representation of the identity of the Toraja traditional community in the stages of the lantang pangngan ritual, namely social status as the basis of ma'lantang pangngan, Pa'pakatu: representation of social values and love, and Tengko situru': the cultural identity of togetherness in joys and sorrows.